Complex Interactions between soil-transmitted helminths and malaria in pregnant women on the Thai-Burmese border. - Machteld Boel; Verena I Carrara; Marcus Rijken; Stephane Proux; Mathieu Nacher; Mupawjay Pimanpanarak; Moo Koo Paw; Oh Moo; Hser Gay; Wendi Bailey; Pratap Singhasivanon; Nicholas J White; et al. (PLoS Neglected Tropical Diseases, 2010)
Deworming is recommended by the WHO in girls and pregnant and lactating women to reduce anaemia in areas where hookworm and anaemia are common. There is conflicting evidence on the harm and the benefits of intestinal geohelminth infections on the incidence and severity of malaria, and consequently on the risks and benefits of deworming in malaria affected populations. We examined the association between geohelminths and malaria in pregnancy on the Thai-Burmese border.Routine antenatal care (ANC) included active detection of malaria (weekly blood smear) and anaemia (second weekly haematocrit) and systematic reporting of birth outcomes. In 1996 stool samples were collected in cross sectional surveys from women attending the ANCs. This was repeated in 2007 when malaria incidence had reduced considerably. The relationship between geohelminth infection and the progress and outcome of pregnancy was assessed.Stool sample examination (339 in 1996, 490 in 2007) detected a high prevalence of geohelminths 70% (578/829), including hookworm (42.8% (355)), A. lumbricoides (34.4% (285)) and T.trichuria (31.4% (250)) alone or in combination. A lower proportion of women (829) had mild (21.8% (181)) or severe (0.2% (2)) anaemia, or malaria 22.4% (186) (P.vivax monoinfection 53.3% (101/186)). A. lumbricoides infection was associated with a significantly decreased risk of malaria (any species) (AOR: 0.43, 95% CI: 0.23-0.84) and P.vivax malaria (AOR: 0.29, 95% CI: 0.11-0.79) whereas hookworm infection was associated with an increased risk of malaria (any species) (AOR: 1.66, 95% CI: 1.06-2.60) and anaemia (AOR: 2.41, 95% CI: 1.18-4.93). Hookworm was also associated with low birth weight (AOR: 1.81, 95% CI: 1.02-3.23).A. lumbricoides and hookworm appear to have contrary associations with malaria in pregnancy.